EVALUASI MANAJEMEN KEBENCANAAN PADA CAGAR BUDAYA STUDI KASUS KOTA PADANG, SUMATERA BARAT - , Alfa Noranda, Dr. Daud Aris Tanudirjo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The City of Padang has at least 74 heritages and three historical areas enlisted on Mayorâs Decree. However, as Padang situated in the area susceptible to disasater, those heritage are disposed to potensial damage and loss due to natural as well as human-made disaster. The potensialn become higher as no standard procedure of disaster-risk management are available both at the city level and national alike. This research aim to evaluate the implementation of disaster-risk management, as part of cultural resource management, after an earthquake hit the City of Padang in 2009. In this research some analysis were conducted including model, comparative, historical, and geo-spatial. As the first step in evaluation process, a model for disaster-risk management was set up as a parameter for evaluation. The model was built base on comparative study on several available models, i.e Indonesian Law no. 24 on Managing Disaster, Ministiry of Culture and Tourism Regulation no. 64/UM.001/MKP/2009 on the Guideline for Post-Disaster Handling of Heritage, Managing Disaster Risk for World Heritage published by World Heritage Center UNESCO, and Guideline for Managing Post-Disaster : Conservation of Heritage Building published by Indonesian Heritage Trust (Badan Pelestari Pusaka Indonesia). The result show that procedure for handling heritage during the post- Padang Earthquake 2009 was not conducted according to the standard procedure of disater-risk management. There were some steps which not implemented orderly as stipulated by the standard procedure. Some processes in the pre-disaster stage have never been carried out. Thus, all the actions conducted were not appropriate. This means that in the future all stakeholders involve in the risk-disaster management should conduct the standard procedure more properly to minimize the damage or lost of the heritage.